How government internal control system supporting regional development goals: Empirical evidence from internal control system in Indonesia - Indrawan Firdauzi; Agus Arifin; Muhammad Farid Alfarisy; Pahrul Fauzi; Lilis Siti Badriah; Ajeng Faizah Nijma Ilma; Nani Kartika Ulina Nasution (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
This study provides an empirical understanding of how integrated internal government controls in Indonesia can support regional development goals. Using Path analysis, we test the relationship between government internal control systems, budget efficiency, and regional development, with emphasis on health, education, and poverty. Surprisingly, the study revealed that instruments within the government's internal control systems, the corruption prevention effectiveness index, and the government's internal oversight positively impacted budget efficiency. However, we found that the risk management index negatively affected budget efficiency. In conclusion, this study establishes a link between internal government control, budget efficiency, and development goals. These findings underscore the importance of implementing high-quality internal oversight to support regionalized national development objectives.Keywords: SPIP, Government Internal Supervision, Indonesia, Budget Efficiency, Development Goals.